Lands and peoples. The world in color. Volume 5 : Africa, Australia, Oceania - Merrick, Helen Hynson
Morocco -- Sub-Sahara Africa -- Algeria, Tunisia and Libya -- Egypt's relics -- The Sphinx and the Pyramids -- Egypt -- Cairo -- Sudan Republic -- Liberia and Ethiopia -- Emerging african states -- Congo Basin -- Southern Africa -- Malagasy Republic -- Indonesia -- Borneo -- New Guinea -- The Pacific islands -- Philippine Republic -- Australia -- Australia's aborigines -- New Zealand -- The Maoris